Trends and Gaps in Islamic Education Research in Indonesia: A Bibliometric Approach - Azma Azma; Salahuddin Salahuddin; Wiwin Mistiani; Rustina Rustina (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study aims to identify publication trends, key actors, thematic focuses, and research gaps in Islamic Education in Indonesia for the 2014–2025 period through a bibliometric approach. Using the PRISMA protocol, data were retrieved from Scopus using relevant keywords and analyzed with VOSviewer. Of the 884 initial documents, 380 documents were filtered that met the analysis criteria. The results show a sharp increase in publications since 2019, in line with the internationalization policy of higher Education and the accelerated adoption of digital learning technologies. The most influential authors are Zalik Nuryana and Suyadi, while the Journal of Islamic Education and Cogent Education are the publication channels with the highest impact. International collaborations are dominated by partnerships between Indonesia and Malaysia, with involvement from Australia, Brunei Darussalam, and China. Keyword analysis shows the dominance of the themes of Islamic Education, Religious Moderation, and Islamic Boarding Schools, with the emergence of new themes such as digital learning, gender equality, and multicultural Education. The mapping also identified seven key gaps, including weak pedagogical innovation, a descriptive approach to religious moderation, unsustainable digitalization, marginalization of gender issues, limited research on child protection and the welfare of Islamic boarding school students (santri), poor integration with the Sustainable Development Goals (SDGs), and limited research on interdisciplinarity. This study recommends strengthening the integration of digital pedagogy, developing a moderation model based on evaluative instruments, mainstreaming gender, and expanding global collaboration. The research's novelty lies in the full integration of the PRISMA and VOSviewer methods to produce a comprehensive, evidence-based thematic mapping, thus providing a methodological and strategic foundation for developing a more innovative and internationally competitive research agenda in Indonesian Islamic Education.